Impact of maternal and offspring smoking and breastfeeding on oesophageal cancer in adult offspring - Yixue Wang; Hongru Sun; Gen Li; Jingxue Xu; Siyu Wang; Shijie Zhang; Tianle Zhou; Tianshu Han; Changhao Sun; Jianqun Ma; Xiaoyuan Wang; Hang Yin (Nature Communications)
Abstract Numerous risk factors for oesophageal cancer are linked to lifestyle habits, but the role of early-life factors in its incidence and mortality is unclear. Using UK Biobank data, we explore the association among breastfeeding, maternal smoking, smoking in offspring, and oesophageal cancer risk in adult offspring via multivariable Cox regression. Here, we show that being breastfed, compared with not being breastfed, is associated with a lower risk of oesophageal cancer incidence (HR: 0.83, 95% CI: 0.70–0.98) and mortality (HR: 0.74, 95% CI: 0.61–0.89) in adult offspring. Additionally, it is associated with a reduced impact of smoking in offspring on oesophageal cancer incidence (HR: 0.79, 95% CI: 0.64-0.96) and mortality (HR: 0.73, 95% CI: 0.59-0.91). We subsequently construct a polygenic risk score for oesophageal cancer to explore the influence of genetic factors. Our findings emphasize the importance of breastfeeding, and smoking cessation to prevent oesophageal cancer.